Reviews of events - HISULA, Investigadores Grupo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this section you will find reviews of scientific events related to the history of the Latin American education.